Associations Between Physical Activity and Gross Motor Skills with Social Development in Children with Learning Disabilities - Eliassy, Marzieh; Khajavi, Daryoush; Shahrjerdi, Shahnaz; Mirmoezzi, Masoud (International journal of sport studies for health, 2021)
Background: Social development is a fundamental aspect of motor development in children. It has been shown that children with learning disorders have different gross motor skills and physical activity compared to typically developing peers. Objectives: Since developmental domains interact with each other and children with learning disabilities often have difficulties that go far beyond those in school homework, the purpose of this study is to investigate the relationship between physical activity and gross motor skills with social development for children with learning disabilities. Methods: In children with learning disorder (n = 82; 49 boys, 33 girls), gross motor skills and physical activity were assessed respectively with the Test of Gross Motor Development-2 and Past Year Physical Activity Questionnaire. Vineland Social Maturity Scale was used to evaluate the social development of participants. The Pearson correlation coefficient is used to association between variables. The significance for test was set at P < 0.05. Results: Locomotor and object-control were significantly associated with social development (r = 0.60, P < 0.001) and (r = 0.44, P = 0.003), respectively. Organized activities were significantly associated with social development (r = 0.69, P = 0.001). Also, gross motor skills and organized activities were able to predict the social development of children with learning disorder (R2 = 0.29, F = 15.78). Conclusions: Children with higher levels of organized activities and motor skills had higher social development. As a result, gross motor skills and organized physical activity are especially important for children with learning disabilities.